The relationship between dental age, bone age and chronological age in underweight children - Vinod Kumar; Karthik Venkataraghavan; Ramesh Krishnan; Kavitha Patil; Karishma Munoli; Sandhya Karthik (Wolters Kluwer Medknow Publications, 2013)
Background and Objective: The knowledge of bone age and dental age is of great importance for pediatrician and pediatric dentist. It is essential for a pediatric dentist to formulate treatment plan and it is a source of complementary information for pediatrician. There are few studies, which showed the relationship between dental age, bone age and chronological age in underweight children. Therefore, objective of this study was to determine and compare dental age, bone age and chronological age in underweight children. Materials and Methods: 100 underweight children between the age group of 18-14 years were selected. Chronological age was assessed by recording date of birth. Dental age assessment was done using orthopantamogram following the method described by Demirjian. Bone age assessment was carried out using hand wrist radiograph following Bjork, Grave and Brown's method. Results: Dental age and Bone age was delayed compared to chronological age in both sexes. The correlation between chronological age, dental age and bone age were all positive in males. Interpretation and Conclusion: The data supports the concept that dental age and bone age delay is a significant feature in underweight children. It is important to consider dental age and bone age as variables for diagnosing underweight children. To support our findings further a well-designed, controlled as well as longitudinal studies with a larger sample size is required.